Pentoxifylline as a Therapy for Thin Endometrial Lining in Infertility - Muharam Natadisastra; Riyan H Kurniawan; Devi M Malik (Indonesian Socety of Obstetrics and Gynecology, 2015)
Objective: To evaluate the effect of pentoxifylline as a single regimen therapy for thin endometrial lining in infertility. Method: A cross-sectional retrospective research was held in Yasmin Clinic - Kencana, Dr. Cipto Mangunkusumo Hospital from 2010 until 2011. Our respondents were women with infertility problem. Result: There was significant improvement of endometrial lining in respondents who received pentoxifylline in the first month (p